Upaya Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran PKN Melalui Model Pembelajaran Kooperatif TGT (Team Game Tournaments) Pada Siswa UPTD SDN Blega I - Atthiana Marpa; Budiyono Budiyono; Siti Komariyah (International Forum of Researchers and Lecturers, 2023)
The problem in the study carried out is that it provides an understanding regarding student learning in Civics learning which is still not good, especially because the teacher only uses the classroom environment and places more emphasis on taking notes from textbooks. In addition, student participation in asking and answering questions during learning activities is still lacking, which makes them less motivated to learn. Using the Teams Games Tournament approach, this study aims to improve Civics learning outcomes and student involvement in the learning process in class IV SDN Blega 1 unit